Gender parity in German politics: Further effort required - Daniela Arregui Coka; Ronny Freier; Johanna Mollerstrom (DIW Economic Bulletin, 2017)
Although many political authorities endorse the basic goal of parity between men and women across the board, reality does not yet reflect this in Germany. In the German Bundestag, for example, at present 37.1 percent of representatives are women. Divided among the six parties with the greatest likelihood of being elected to the Bundestag, a total of 1,979 people are running for office in the upcoming election. Of these, 35.7 percent are women. An analysis of the lists of candidates by party shows that the parties currently represented in the Bundestag have significantly higher proportions of women among their candidates than the opposition parties FDP and AfD do. In the top 48 slots-that is, the first three on each of the 16 state lists-the Green Party is putting forward 32 women, the Left Party 27, and the SPD 25. With 15 female candidates for office, the Union Parties (CDU/CSU) are also higher than the FDP and AfD (with 11 and eight candidates respectively). Of the 263 ministerial posts available since Germany was founded, women have only held 43. Although Germany has a female chancellor and the gender distribution in the current cabinet is almost equal, certain ministerial posts have yet to be held by a woman. The government resulting from the upcoming Bundestag election could serve as an example by explicitly committing itself to gender parity. In state parliaments, women are more underrepresented than on the national level. In the former, the proportion of women is 31 percent and has recently fallen. Only three out of 16 regional governments are headed by a woman. An international comparison shows that extended use of voluntary quotas for the parties-as already practiced in Germany-could be a highly viable way of achieving parity. They would be more effective if consistently implemented by all at all levels. And voters can make a difference by demanding equal representation from the parties.
Keywords: J16; D72; 330; women in politics; female participation; political representation